Oak trees and soil interactions in Mediterranean forests: a positive feedback model - Aponte, Cristina; García, Luis V.; Pérez-Ramos, Ignacio M.; Gutiérrez, Eduardo; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the spectrum of variability of chemical elements in a Mediterranean forest ecosystem across the different compartments? Do coexisting tree species with different leaf chemical composition and nutrient cycling distinctly modify soil conditions? Could these species-speciﬁc, treegenerated soil changes create a potential positive feedback by affecting longterm species distribution? Location: Mixed oak forests of southern Spain, Los Alcornocales Natural Park. Methods: We sampled and chemically analysed ﬁve different ecosystem components: leaves, leaf fall, litter and superﬁcial (0–25 cm) and sub-superﬁcial (25–50 cm) soil beneath the canopies of evergreen Quercus suber and deciduous Q. canariensis trees. We used multiple co-inertia analysis (MCoA) to conjointly analyse the patterns of variability and covariation of eight macro- and micronutrients determined in each of the sampled ecological materials. We implemented a path analysis to investigate alternative causal models of relationships among the chemical properties of the different ecosystem components. Results: Variability in the concentration of chemical elements was related to the nature of their biogeochemical cycles. However, the rank of element concentration was consistent across ecosystem components. Analysis of coinertia (MCoA) revealed that there was a common underlying multivariate pattern of nutrient enrichment in the ecosystem, which supported the hypothesis of a separation in biogeochemical niches between the two co-existing oak species, with Q. canariensis having richer plant tissues and more fertile soil directly under each tree than Q. suber. The feasibility of a potential tree–soil positive feedback model was the only statistically validated among several alternative (non-feedback) models tested. Conclusions: In the studied Mediterranean forests, oak species distinctly modify soil fertility conditions through different nutrient return pathways. Further investigation is needed to address whether these tree-generated soil changes could affect seedling establishment and ultimately inﬂuence species distribution.
Keywords: Biogeochemical niche; ecological stoichiometry; ecosystem functioning; Foliar analysis; nutrient cycling; Quercus canariensis; Quercus suber; Soil fertility

Responses of photosynthesis to high temperatures in oak saplings assessed by chlorophyll-a fluorescence: inter-specific diversity and temperature-induced plasticity - Daas, C; Montpied, P; Hanchi, B; Dreyer, E (Annals of forest science, 2008)
• The sensitivity of photosynthesis to high temperature was investigated in greenhouse-grown saplings of three Mediterranean (Quercus canariensis Willd., Q. coccifera L. and Q. suber L.) and two temperate European oak species (Q. robur L. and Q. petraea Matt. Liebl.). The sensitivity to high temperature was inferred from F0T curves producing the critical temperature (Tc ) at which a rapid rise in ground chlorophyll a ﬂuorescence (F0) occurs. Tc is known to acclimate to moderately increased ambient temperature by displaying signiﬁcant increases. • We ﬁrst checked whether acclimation of Tc was paralleled by an increase in optimal temperature for light driven electron ﬂux (Topt ,), recorded by measuring quantum yield of photochemistry under saturating CO2 and moderate irradiance. Saplings of Q. suber and Q. canariensis were submitted to four, ﬁve days long ambient temperature steps (15, 25, 35 and 15 ◦ C again). Tc was usually largely above 45 ◦ C while Topt was around 30–35 ◦ C. Both increased with ambient temperature in the two species, and decreased again when temperature returned to the initial values. This recovery was nevertheless not complete after a week at 15 ◦ C. • A second experiment tested whether the plasticity of Tc was of the same extent in the ﬁve species. A signiﬁcant increase of Tc followed by a decrease was detected in all species. Only small inter-speciﬁc diﬀerences were detected in Tc , and temperature induced plasticity was similar in the diﬀerent species: Tc increased by about 4–5 ◦ C while ambient temperature was increased from 15 to 35 ◦ C. Mediterranean and European oaks did not diﬀer in this respect. • This result does not support the hypothesis that oak species from warmer regions would display a larger plasticity of Tc in response to increasing temperatures.
Keywords: optimal temperature; Photochemistry; quantum yield; Quercus canariensis; Quercus coccifera; Quercus petraea; Quercus robur; Quercus suber

Responses of photosynthesis to high temperatures in oak saplings assessed by chlorophyll-a fluorescence: inter-specific diversity and temperature-induced plasticity - Daas, C.; Montpied, P.; Hanchi, B.; Dreyer, E. (Annals of forest science, 2008)
• The sensitivity of photosynthesis to high temperature was investigated in greenhouse-grown saplings of three Mediterranean (Quercus canariensis Willd., Q. coccifera L. and Q. suber L.) and two temperate European oak species (Q. robur L. and Q. petraea Matt. Liebl.). The sensitivity to high temperature was inferred from F0T curves producing the critical temperature (Tc ) at which a rapid rise in ground chlorophyll a ﬂuorescence (F0) occurs. Tc is known to acclimate to moderately increased ambient temperature by displaying signiﬁcant increases. • We ﬁrst checked whether acclimation of Tc was paralleled by an increase in optimal temperature for light driven electron ﬂux (Topt ,), recorded by measuring quantum yield of photochemistry under saturating CO2 and moderate irradiance. Saplings of Q. suber and Q. canariensis were submitted to four, ﬁve days long ambient temperature steps (15, 25, 35 and 15 ◦ C again). Tc was usually largely above 45 ◦ C while Topt was around 30–35 ◦ C. Both increased with ambient temperature in the two species, and decreased again when temperature returned to the initial values. This recovery was nevertheless not complete after a week at 15 ◦ C. • A second experiment tested whether the plasticity of Tc was of the same extent in the ﬁve species. A signiﬁcant increase of Tc followed by a decrease was detected in all species. Only small inter-speciﬁc diﬀerences were detected in Tc , and temperature induced plasticity was similar in the diﬀerent species: Tc increased by about 4–5 ◦ C while ambient temperature was increased from 15 to 35 ◦ C. Mediterranean and European oaks did not diﬀer in this respect. • This result does not support the hypothesis that oak species from warmer regions would display a larger plasticity of Tc in response to increasing temperatures.
Keywords: optimal temperature; Photochemistry; quantum yield; Quercus canariensis; Quercus coccifera; Quercus petraea; Quercus robur; Quercus suber

Seed removal in two coexisting oak species: ecological consequences of seed size, plant cover and seed-drop timing - Pérez-Ramos, Ignacio M.; Urbieta, Itziar R.; Marañón, Teodoro; Zavala, M. A.; Kobe, Richard K. (Oikos, 2008)
Seed predation and dispersal can critically influence plant community structure and dynamics. Inter-specific differences arising at these early stages play a crucial role on tree recruitment patterns, which in turn could influence forest dynamics and species segregation in heterogeneous environments such as Mediterranean forests. We investigated removal rates from acorns set onto the ground in two coexisting Mediterranean oak species –Quercus canariensis and Q. suber– in southern Spain. We developed maximum likelihood estimators to investigate the main factors controlling probabilities of seed removal and to describe species-specific functional responses. To account for inter-specific differences in seed-drop timing, two experiments were established: a simultaneous exposure of acorns of the two species (synchronous experiments) and a seed exposure following their natural seed-drop phenology (diachronic experiments). A total of 1536 acorns were experimentally distributed along a wide and natural gradient of plant cover, and removal was periodically monitored for three months at two consecutive years (with contrasting differences in seed production and thus seed availability on the ground). The probability of seed removal increased with plant cover (leaf area index, LAI) for the two oak species. Inter-specific differences in acorn removal were higher in open areas and disappeared in closed microhabitats, especially during a non-mast year. Despite later seed-drop, Q. suber acorns were removed faster and at a higher proportion than those of Q. canariensis. The higher probability of seed removal for this species could be attributed to its larger seed size compared to Q. canariensis, as inter-specific differences were less pronounced when similar sized acorns were exposed. Inter-specific differences in seed removal, arising from seed size variability and microsite heterogeneity, could be of paramount importance in oak species niche separation, driving stand dynamics and composition along environmental gradients.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: plant cover (voyant); Quercus canariensis; Quercus suber; Seed removal; Seed size

Seed removal in two coexisting oak species: ecological consequences of seed size, plant cover and seed-drop timing - Pérez-Ramos, Ignacio M; Urbieta, Itziar R; Marañón, Teodoro; Zavala, M A; Kobe, Richard K (Oikos, 2008)
Seed predation and dispersal can critically influence plant community structure and dynamics. Inter-specific differences arising at these early stages play a crucial role on tree recruitment patterns, which in turn could influence forest dynamics and species segregation in heterogeneous environments such as Mediterranean forests. We investigated removal rates from acorns set onto the ground in two coexisting Mediterranean oak species –Quercus canariensis and Q. suber– in southern Spain. We developed maximum likelihood estimators to investigate the main factors controlling probabilities of seed removal and to describe species-specific functional responses. To account for inter-specific differences in seed-drop timing, two experiments were established: a simultaneous exposure of acorns of the two species (synchronous experiments) and a seed exposure following their natural seed-drop phenology (diachronic experiments). A total of 1536 acorns were experimentally distributed along a wide and natural gradient of plant cover, and removal was periodically monitored for three months at two consecutive years (with contrasting differences in seed production and thus seed availability on the ground). The probability of seed removal increased with plant cover (leaf area index, LAI) for the two oak species. Inter-specific differences in acorn removal were higher in open areas and disappeared in closed microhabitats, especially during a non-mast year. Despite later seed-drop, Q. suber acorns were removed faster and at a higher proportion than those of Q. canariensis. The higher probability of seed removal for this species could be attributed to its larger seed size compared to Q. canariensis, as inter-specific differences were less pronounced when similar sized acorns were exposed. Inter-specific differences in seed removal, arising from seed size variability and microsite heterogeneity, could be of paramount importance in oak species niche separation, driving stand dynamics and composition along environmental gradients.
Keywords: plant cover (voyant); Quercus canariensis; Quercus suber; Seed removal; Seed size

Ecology and history of a wooded landscape in southern Spain - MARAÑÓN, T; Ojeda, J F (ECOLOGICAL HISTORY OF EUROPEAN FORESTS, 1998)
An extensive oak woodland, of about 1000 km(2), dominated by evergreen cork oak (Quercus suber) and semideciduous Q. canariensis, is found in southern Spain, near the Strait of Gibraltar, and contrasts with the paradigm of deforested Mediterranean mountains. Several factors, ecological, geographical and historical, have contributed to the origin and maintenance of this forested landscape. The rough relief and the acidic, nutrient-poor soils (derived from Oligo-Miocene sandstone) made this area unsuitable for cultivation. The oceanic influence favours the growth of oak trees. In particular, the cork oak is well suited to acidic soils and the humid Mediterranean climate. Three historical milestones seem relevant to the preservation of this woodland. Its location at a frontier during medieval times (thirteenth to fifteenth centuries) discouraged villages and reduced human pressure on the woodland resources. The rise of the value of cork helped to preserve the cork oak woodland during early nineteenth. century industrial times. contemporary consciousness about the conservation of woodland landscapes (somewhat unusual in the Mediterranean region) led to their designation as Los Alcornocales (meaning `The cork oak woodlands') Natural Park, devoted to the eco-development of the region.
Keywords: Cork oak; forest landscape; human pressure; Mediterranean climate; Oak woodlands; Quercus canariensis; Quercus suber